ANALISIS RATA-RATA, MEDIAN, DAN VISUALISASI JUMLAH KEPALA SEKOLAH DAN GURU BERDASARKAN KELOMPOK UMUR DI PROV. LAMPUNG, PROV. RIAU, PROV. ACEH, PROV. PAPUA BARAT - Hibatullah Dzaky Ikram Hakim; Ahmad Yusuf Syaifullah; Agung Januardi; Henry Mufid (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This journal analyzes data on the number of school principals and teachers in four provinces in Indonesia (Lampung, Riau, Aceh, and West Papua) by age group. The analysis was carried out by calculating the average and median scores of the number of principals and teachers in each age group. Data visualization was also carried out in the form of histograms, frequency polygons, and ogive to show the distribution and distribution of the number of educators by age group in each province.